PEDAGOGICAL-PSYCHOLOGICAL FOUNDATIONS OF THE DEVELOPMENT OF SOCIAL COMPETENCE IN STUDENTS - Shomurodov Jamshid Olimboy ugli (Sciental Journals Publishing, 2025)
In this article, the pedagogical and psychological foundations of the development of social competence of young people are widely analyzed. The essence of the concept of social competence, the stages of its formation, the components and mechanisms of interaction between teachers and psychologists in this process are highlighted. At the same time, recommendations have been developed on the basis of educational technologies, methods and methods that contribute to the active integration of young people into public life.
Keywords: Youth, social competence, education, upbringing, pedagogical approach, psychological development, communicative competence, reflection, empathy.